PENGARUH PENGGUNAAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN BELAJAR READING COMPREHENSION DI SMK KELAS XI - Yoga Pratama (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2017)
Mind mapping is method they can help students in every subject. Mind mapping is a beneficial learning tool to help students brainstorm any topic and think creatively. Mind maps are particularly helpful in the writing and reading process and provide students with a natural way of thinking and building thoughts on a story plot or theme in reading comprehension. Mind maps also provide teachers with insight into their students’ thought process regarding a specific topic. By asking students to create mind maps demonstrating their comprehension of a concept, teachers are able to understand what a student’s prior knowledge was and how well the student understands the assignment or the material being taught. This is a very effective way of evaluating students’ understanding.Keywords: mind mapping, students, effective